Precise Land Evaluation Implementation of the Regional Spatial Plan in the Sleman Regency to Maintain Human Health and Food Security - Wahyuti, Isnaeni Sri; Zulaika, Isti; Supriyadi, Supriyadi; Tonabut, Wasuthon (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2023)
Agricultural land in Sleman Regency has changed many functions, including constructing toll roads and settlements. The conversion of agricultural land to non-agricultural land, without being balanced by the creation of new farmland, resulted in the threat of crisis. This research aims to adjust the spatial plan and its application in the field to suppress and control the rate of agricultural land conversion, thus supporting the maintenance and the realization of food security and good health. It was implemented in the Sleman Regency area covering 17 sub-districts. This research uses the institutional survey method, which collects secondary data from development policies and programs from relevant agencies via email, website or coming directly to the office. The results show that the total area of agricultural land conversion in Sleman Regency is 69.93 ha per year. Agricultural land needs to increase its size by 356 ha in 2019 to meet the demands of the applicable laws and regulations. Land use unrelated to the area's function can impact ecological imbalances and potential disasters. Efforts to optimize land use include land certification, granting, signage and tightening permits. Finally, this research study concluded that by optimizing land use, it is hoped that it will be able to maintain and realize food security and good health, especially in Sleman Regency.